Question -
Answer -
Given
We know that if two matrices are equal then the elements of eachmatrices are also equal.
Given that two matrices are equal.
Therefore by equating them we get,
2a + b = 4 …… (1)
And a – 2b = – 3 …… (2)
And 5c – d = 11 …… (3)
4c + 3d = 24 …… (4)
Multiplying equation (1) by 2 and adding to equation (2)
4a + 2b + a – 2b = 8 – 3
⇒ 5a= 5
⇒ a= 1
Now, substituting the value of a in equation (1)
2 × 1 + b = 4
⇒ 2+ b = 4
⇒ b= 4 – 2
⇒ b= 2
Multiplying equation (3) by 3 and adding to equation (4)
15c – 3d + 4c + 3d = 33 + 24
⇒ 19c= 57
⇒ c= 3
Now, substituting the value of c in equation (4)
4 × 3 + 3d = 24
⇒ 12+ 3d = 24
⇒ 3d= 24 – 12
⇒ 3d= 12
⇒ d= 4
∴ a= 1, b = 2, c = 3 and d = 4